2007
DOI: 10.1007/s11701-007-0014-1
|View full text |Cite
|
Sign up to set email alerts
|

Surgical techniques: robot-assisted laparoscopic myomectomy with the da Vinci® surgical system

Abstract: Myomectomy remains the surgical option of choice for women with symptomatic leiomyomata who desire uterine conservation or in particular future fertility. The ability to enucleate leiomyomata and repair the uterus with a multilayer-sutured closure is both crucial and technically challenging. Advanced gynecologic pathology and the surgical limitations of conventional laparoscopy have often been cited as impediments to not only these critical steps but also to converting a myomectomy from a procedure predominant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 7 publications
0
15
0
1
Order By: Relevance
“…The technique of the robotic-assisted laparoscopic myomectomy used in these two studies is explained in detail. 94 A case of a robot-assisted enucleation of a large myoma is described by Mao et al 95 Sroga et al described 15 women in whom they performed a robot-assisted myomectomies and found operative time to range from 159 to 389 minutes, with an average blood loss of 160 mL. 96 In a retrospective matched control study of 15 cases comparing robot-assisted laparoscopic myomectomy and laparoscopic myomectomy, no difference in blood loss, hospital stay and postoperative complications was found.…”
Section: Tubal Reanastomosismentioning
confidence: 99%
“…The technique of the robotic-assisted laparoscopic myomectomy used in these two studies is explained in detail. 94 A case of a robot-assisted enucleation of a large myoma is described by Mao et al 95 Sroga et al described 15 women in whom they performed a robot-assisted myomectomies and found operative time to range from 159 to 389 minutes, with an average blood loss of 160 mL. 96 In a retrospective matched control study of 15 cases comparing robot-assisted laparoscopic myomectomy and laparoscopic myomectomy, no difference in blood loss, hospital stay and postoperative complications was found.…”
Section: Tubal Reanastomosismentioning
confidence: 99%
“…Advincula et al ont décrit la myomectomie assistée par robot avec le système da Vinci [48][49][50]. Sur 35 cas, le taux de conversion était de 8,6 %, ce qui était comparable au taux retrouvé en coelioscopie dans la littérature (0 à 28,7 %) [51][52][53][54].…”
Section: Myomectomieunclassified
“…In Germany the use of the robotic system in gynaecological care is only at the beginning of a promising development. The spectrum of indications includes simple hysterectomies, above all in patients with uterine fibroids, with history of several previous abdominal operations, salpingoophorectomy in larger adnexal masses, interventions in extensive endometriosis, sacrocolpopexies, myomectomies (1,47,61), tubal reanastomosis and mainly the modified radical and radical hysterectomies (10, 20-22, 33, 41, 48, 49, 51, 53) in early stages of endometrial (16,25,26,28,31,32,36,37,50,(58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69) and cervical cancer (12,42,65), especially nerve sparing radical hysterectomy, including pelvic and paraaortic, respectively upper paraaortic lymph node dissection, but also with less frequency trachelectomy, parametranectomy (3,11,14,52,54,55), interventions in early ovarian cancer (30,40), pelvic exenteration (15,35), colposuspension and the lateral colpopexy via transperitoneal approach (19,63,64), interventions in uterine malformations, and others (23). Many of these indic...…”
Section: Introductionmentioning
confidence: 99%